"DUAL EDUCATION AND INDUSTRY PARTNERSHIPS: A PATHWAY TO INNOVATIVE TEACHING AND COMPETENCY GROWTH IN TECHNICAL FIELDS," - Alibekova Mokhira Abduvaliyevna (International Journal of Literature and Language Studies, 2026)
This research examines the advantages, challenges, and overall effectiveness of implementing the dual education system in technical schools in Uzbekistan. Using analytical, statistical, interview, and experimental methods, the study evaluates both international experiences and local practices. Results show that dual education strengthens the integration of theoretical and practical training, increases graduate employment by 15–20%, and helps alleviate the shortage of qualified personnel. Key challenges, such as weak school–enterprise cooperation, insufficient safety provisions, and limited availability of qualified mentors—remain barriers to system expansion. The study provides recommendations for improving policy, enhancing collaboration with enterprises, and modernizing vocational education standards.